ANALISIS KEBERHASILAN SISTEM REWARDS DAN PUNISHMENTS DALAM MENINGKATKAN KINERJA KARYAWAN - Nabila Dwiputri Gunawan; Resya Dwi Marselina (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2026)
This study aims to analyze the effectiveness of the reward and punishment system in improving employee performance at PT. Tunas Dwipa Matra. The background of this study is based on the importance of human resource management through the implementation of rewards and sanctions to increase motivation, discipline, and work productivity. However, based on company data from 2022–2024, fluctuations in employee performance and an increase in disciplinary violations were still found. This study used a qualitative approach with a descriptive method through data collection techniques consisting of interviews, observations, and documentation involving informants selected through purposive sampling from management and employees. The results showed that the reward system, in the form of bonuses, incentives, best employee awards, and career development opportunities, was able to increase work enthusiasm, responsibility, and employee motivation, while the punishment system, in the form of verbal warnings, written warnings, and administrative sanctions, played a role in enforcing work discipline. However, there were still obstacles such as perceptions of unfairness, lack of transparency, and inconsistency in policy implementation. The conclusion of this study indicates that the reward and punishment system has contributed to improving employee performance, but its effectiveness has not been optimal. Therefore, the company needs to improve objectivity, transparency, and consistency in order to create a fair and productive work environment. Keywords: Reward, Punishment, Employee Performance.